The Intersection Graph of a Dihedral Group - Nurhabibah Nurhabibah; Abdul Gazir Syarifudin; I Gede Adhitya Wisnu Wardhana; Qurratul Aini (Eigen Mathematics Journal, 2021)
The intersection graph of a finite group G is a graph (V,E) where V is a set of all non-trivial subgroups of G and E is a set of edges where two distinct subgroups H_i , H_j are said to be adjacent if and only if H_i \cap H_j ≠ {e} . This study discusses the intersection graph of a dihedral group D_{2n} specifically the subgraph, degree of vertices, radius, diameter, girth, and domination number. From this study, we obtained that if n=p^2 then the intersection graph of D_{2n} is containing complete subgraph K_{p+2} and γ(Γ_{D_{2n}})=p.